An Unusual Case of Recurrent Guillain-Barre Syndrome of a Different Subtype Five Years after Initial Diagnosis. (28th April 2013) - Dy, M.; Leshner, R. L.; Crawford, J. R.
Abstract : We present a case of a previously healthy 17-year-old girl with history of Guillain-Barre Syndrome 5 years after initial presentation who presented with bilateral lower extremity pain, worsening dysphagia, subsequent weakness, and decreased reflexes. Cerebrospinal fluid analysis had a prominent lymphocytic pleocytosis. MRI of spine showed significant anterior nerve root enhancement. Electromyogram demonstrated a mild axonal greater than demyelinating motor polyneuropathy and intact sensory responses, with no evidence of conduction block or temporal dispersion, unlike her first presentation that revealed a demyelinating polyneuropathy. The patient recovered with mild subjective weakness following 5 days of intravenous immunoglobulin treatment. This case represents a recurrence of a predominantly motor variant polyradiculoneuropathy distinct from the initial presentation with a lymphocytic predominant CSF pleocytosis, nerve root enhancement on MRI spine, and rapid recovery following treatment with intravenous immunoglobulin.